(untitled) (Journal of Governance and Development (JGD), 2024)
Government in an ideal society strives to promptly crush security challenges like banditry with a view to safeguarding human rights of the people but regrettably the reverse is the case in Nigeria. This study investigated the effect of rural banditry on human rights in Oyo and Ondo States, Nigeria. The study adopted descriptive survey research design and quantitative method using self-structured questionnaire to collect data. A total of 400 respondents were sampled adopting stratified random sampling technique while ANOVA analysis was used to test the research hypotheses of the study. The study revealed that rural banditry activities violated the freedom of movement, rights to privacy, property, human dignity, liberty and security of life, among other civil and political rights of the people in Oyo and Ondo States. It also disclosed that rural banditry grossly violated the freedom of religion, rights to education, property as well as social and cultural rights of the people in Oyo and Ondo States. The study concluded that rural banditry activities like kidnapping, robbery, village raids, hostage and ransom taking, maiming and murder, among others severely impacted on the rights of people in both Oyo and Ondo States. The study recommended that government should establish special court to try and swiftly deal with the cases of banditry while Amotekun security outfit, which was established to confront the menace should be empowered through intensive training and supply of adequate and modern weapons and equipment.